Climate Change and Its Impact on Agricultural Productivity in the Carpathian Basin: An Econometric Assessment - György Ábrahám (Lembaga Bale Literasi, 2025)
This study examines the impact of climate change on agricultural productivity in the Carpathian Basin, a region spanning Hungary, Romania, Slovakia, Serbia, and Ukraine. Using panel data from 2000 to 2022 and econometric modeling, the research investigates how key climate variables temperature, precipitation, and CO₂ emissions influence crop yields across varying agro-ecological contexts. Secondary data were sourced from FAOSTAT, the World Bank, the European Environment Agency, and national meteorological agencies. Results from fixed effects regression models reveal that rising temperatures significantly reduce crop yields, particularly for heat-sensitive crops like maize and sunflower, with a 1°C increase linked to an average yield decline of 0.93 tons per hectare. Conversely, a 100 mm increase in annual precipitation corresponds to a 5–7% yield improvement, though extreme rainfall or drought events can negate these benefits. While CO₂ emissions exhibit a slight fertilization effect, their interaction with high temperatures results in further yield reductions. Control variables such as fertilizer use and irrigation show mitigating effects, though their influence remains limited in the face of persistent climate stress. The study highlights the urgent need for region-specific adaptation strategies, including enhanced irrigation infrastructure, climate-resilient crops, and cross-border policy collaboration. These findings contribute to the growing literature on climate-agriculture dynamics and offer actionable insights for strengthening food security and sustainability in the Carpathian Basin.